Research on Data Analysis Application Based on Spark Computing - Yan, Jialu (European Journal of AI, Computing & Informatics, 2025)
With the development of the big data era, how to efficiently process and analyze massive data has become an urgent problem that needs to be solved in various industries. Spark, as an open-source distributed computing framework, quickly emerged as a mainstream tool in data processing due to its excellent in memory data processing capabilities and user-friendly interface. Not only does Spark have efficient computing performance, a rich ecosystem, and comprehensive support for data analysis tasks, but it is also widely used in multiple fields such as data management, machine learning, and real-time analysis. This article will delve into the application of Spark in data analysis platforms, reveal the current challenges faced, and explore corresponding optimization approaches, with the aim of significantly improving the efficiency and overall performance of data analysis.